2019
DOI: 10.1007/s00429-019-01938-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the landscape of human dopamine D2/3 receptors with [11C]raclopride

Abstract: The dopamine D2/3 system is fundamental for sensory, motor, emotional, and cognitive aspects of behavior. Small-scale human histopathological and animal studies show high density of D2/3 dopamine receptors (D2/3DR) in striatum, but also demonstrate the existence of such receptors across cortical and limbic regions. Assessment of D2/3DR BPND in the extrastriatal regions with [11C]raclopride has long been considered unreliable due to the relatively low density of D2/3DR outside the striatum. We describe the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 57 publications
3
32
0
Order By: Relevance
“…In line with this evidence, analyses of the present data showed that median BP ND was significantly higher in all ROIs than in the cerebellar reference region, with the left frontal pole showing the smallest difference from the cerebellar reference area (mean BP ND = 0.1; t = 15, p < .001). Moreover, confirmatory factor modelling on the present dataset has shown strong positive links between BP ND in the ROIs across the hemispheres and among different brain regions that tap known anatomical dopamine subsystems, and less strong associations between regions of different subsystems (Papenberg et al 2017), supporting a division into cortical, striatal, and limbic factors for the purpose of the current study. Thus, we deem the extrastriatal estimates as reliable and reflective of target binding.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…In line with this evidence, analyses of the present data showed that median BP ND was significantly higher in all ROIs than in the cerebellar reference region, with the left frontal pole showing the smallest difference from the cerebellar reference area (mean BP ND = 0.1; t = 15, p < .001). Moreover, confirmatory factor modelling on the present dataset has shown strong positive links between BP ND in the ROIs across the hemispheres and among different brain regions that tap known anatomical dopamine subsystems, and less strong associations between regions of different subsystems (Papenberg et al 2017), supporting a division into cortical, striatal, and limbic factors for the purpose of the current study. Thus, we deem the extrastriatal estimates as reliable and reflective of target binding.…”
Section: Methodssupporting
confidence: 54%
“…More advanced measures of D 2/3 R availability than BP ND measured by a single 11 C-raclopride-PET scan at rest would also be useful, particularly measures that allow for teasing apart receptor density and endogenous dopamine levels (Seeman et al 1989; Yoder et al 2008). Further, although recent evidence supports the reliability and validity of extrastriatal measurements of D 2/3 R availability with 11 C-raclopride (Alakurtti et al 2015; Papenberg et al 2017), it is possible that partial-volume effects may to some degree bias the measurements. Importantly, however, we think that these measurement imperfections are unlikely to explain our main result as class 2 and 3 did not differ much (and not statistically) in grey matter volume.…”
Section: Discussionmentioning
confidence: 99%
“…85 Finally, 11C-raclopride binding was found to be organized according to anatomical and functional DA pathways, which further supports the validity of extrastriatal 11 C-raclopride measurements. 86…”
mentioning
confidence: 99%
“…They conceptualized the agerelated attenuation of dopaminergic modulation as an alteration of the activation function of units in a neural network, leading a reduced fidelity of neural information processing and reductions in the distinctiveness of representations. Evidence of reliable individual differences in D2/D3 dopamine receptors in occipital cortex (Papenberg et al, 2019) supports the idea that their availability in early sensory regions could play an important role in neural dedifferentation. Interestingly, recent studies also demonstrated a relationship between a decline of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) and neural distinctiveness.…”
Section: Discussionmentioning
confidence: 61%